From stool to sequence: decoding the human diet with FoodSeq - Dorothy K. Superdock; Brianna L. Petrone; Michelle C. Kirtley; Lawrence A. David (mSystems)
ABSTRACT Diet plays a pivotal role in human health and disease. Yet, nutrition studies have long relied on self-report methods for collecting dietary intake data despite known limitations. Although new technologies for dietary intake assessment and biomarker identification are in development, the integration of genomics has been limited. DNA metabarcoding, a method that identifies many taxa at once using a short region of DNA, has recently been adapted for use in stool samples from free-living humans. This process, called FoodSeq, provides an objective way to determine the foods people eat. FoodSeq has numerous advantages over self-report methods, is a necessary complement to other methodological innovations in dietary intake assessment, and holds considerable promise for application on an epidemiologic scale, enabling more robust analysis of global dietary patterns.